Emergency packets handing in queue aware congestion avoidance schemes in IoHT - Muhammad Zafarullah; Ata Ullah; Sajjad Ahmed Ghauri; Ghalib Muhammad Waqas Janjua (PLoS ONE, 2026)
The Internet of Healthcare Things (IoHT) emerged as an enabling technology that is strongly required for real-time patient monitoring and emergency healthcare services. However, the massive number of messages sent from heterogeneous sensors during the emergency situations generally leads to congestion in the network, causing it to overflow the buffer and lose some vital packets. Existing queue-aware congestion avoidance schemes based on priority queue or FIFO scheduling methods fail to differentiate among several levels of severity in emergency packets, resulting in the delayed or dropped transmission of packets. To addresses the issue of handling the emergency packets in the high and low-priority queues, we propose a scheme called Dual Queue Aware Congestion Avoidance, which operates with a dual queue structure combined with an Emergency-aware Packet Placement Algorithm (EPPA). The scheme classifies packets into high-priority and low-priority queues according to sensor type and assigns an emergency flag to indicate the severity. Unlike conventional FIFO approaches, emergency packets are placed immediately after the currently processed packet to ensure timely treatment without disrupting the ongoing transmission. A large number of simulations are carried out using NS-2.35 on Ubuntu. The results show that D-QACA significantly reduces buffer loss probability and high-priority packet loss—achieving up to 80% lower buffer loss and 90% fewer emergency packet drops compared to state-of-the-art schemes such as QACA and DCCA. The scheme enhances performance through an emergency-aware repositioning mechanism that allows critical packets to be served after the packet currently in processing.